A Review of Iran's Developmental Challenges in the Contemporary International System: A Non-Iranian Perspective - Zekeri Momoh (Richtmann Publishing, 2023)
This research looked at the hurdles to Iran's growth plans in the modern world political economy. The data for this study was gathered from secondary sources such as textbooks, magazine articles, and online sources, and the data was analysed using content analysis. According to this study, Iran has been plagued by violent strife for many years. Furthermore, the mistaken economic policies of earlier Iranian leaders, as well as a reluctance to open the economy to international investors, have contributed to the country's economic stagnation throughout the years. Finally, this study suggests, among other things, that a total shutdown of the Iranian economy in the current global economy will continue to deprive Iran of the myriad economic gains associated with globalisation. Received: 11 October 2022 / Accepted: 30 December 2022 / Published: 5 January 2023